HIGH PERFORMANCE LIQUID CHROMATOGRAPHIC DETERMINATION OF HYDRAZINE IN WATER USING 2-HYDROXYNAPHTHALDEHYDE AS A DERIVATIZING REAGENT (Biological Sciences - PJSIR, 2002)
Hydrazine (HZ) derivative with 2-hydroxyn aphthaldehyde(HN) eluted with methanol: acetonitrile: water (95: 1:4 v/v/v) from reverse phase HPLC column Microsorb C-18, 5µm with  UV  detection  at  330nm.  Hydrazine,  thiosemicarbazide (TSC) and phenylthiosemicarbazide (PTSC) derivatives of HN also separated when eluted with methanol: Chloroform: acetonitrile: water (65:4 :2:29 V/V/V/V) with a flow rate 1 ml/minute, with detection limit in a  ran ge 0.54  to  16 ng/ injection (10µ1). Linear calibration curve for HZ was obtainedwith 0.54-2 .7µg/ml. The effect of variables on the determination  of HZ was  examined  and  method  has been  proposed  for  the determination  of HZ  from water.